Manajemen Pengawasan Tahapan Pemilihan Tahun 2024 - yulianto, yulianto (PT. Karya Inovatif Nusantara, 2024)
Indonesia is a democratic country, one of the indicators of a democratic country is the holding of general elections in the process of filling political positions. The election process in Indonesia is carried out to elect the President and Vice President, DPD, DPR, Provincial DPRD and Regency/City DPRD. In addition, general elections are held to elect the Governor and Deputy Governor, Regent and Deputy Regent or Mayor and Deputy Mayor. The implementation of the Election to elect the President and Vice President, DPD, DPR, Provincial DPRD and Regency/City DPRD in 2024 was held on February 14, 2024. Meanwhile, the election of the Governor and Deputy Governor, Regent and Deputy Regent or Mayor and Deputy Mayor will be held on November 27, 2024. Based on the stages of the implementation of the 2024 regional head elections, Bawaslu needs to analyze the stages of implementation and analyze potential vulnerabilities in the implementation of the 2024 elections. Based on this analysis, it is necessary to prepare preventive measures involving various election stakeholders. The results of this analysis are used as provisions for supervisors at the regional level. Bawaslu Kebumen needs to strengthen the institution internally, emphasizing the importance of mastery of technical matters related to supervision, prevention, dispute resolution, work area analysis, and prevention cooperation efforts through various activities.